Until it Hurts by Mark Hyman - Mark Hyman (Journal of Applied Sports Management, 2010)
The following is an excerpt from author Mark Hyman’s new book Until It Hurts, which focuses on the country’s obsession over youth sports and how this impacts the development of our nation’s youth. Read more about the book at www.untilithurts.com.